Marine Square, Port of Spain, Trinidad - (:unkn) unknown (My University, 2010)
The postcards shows the southern side of Marine Square. On the right is a building with a sign that reads: The Klondy, which was probably a retail store. In the foreground are two beggars. The postcard is postmarked 1936 and affixed are a one and a five cents United States postage stamps. Marine Square was renamed Independence Square in 1962.
Colour: Black and white; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Promenades (Pedestrian areas)--Trinidad and Tobago; Pedestrian areas--Trinidad and Tobago; Architecture--Trinidad and Tobago; Plazas--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Hats--Trinidad and Tobago; Homeless persons--Trinidad and Tobago; Trees--Trinidad and Tobago; 1936; Signs and signboards--Trinidad and Tobago; Shop signs--Trinidad and Tobago; Stores, Retail--Trinidad and Tobago; Marine Square (Port of Spain); Independence Square (Port of Spain)